A história da hermenéutica: uma reflexão a partir do conceito de tradição - Daniel Carreiro Miranda (2016)
The present study aims to elucidate the history of hermeneutics from the reflection of the concept of tradition by hermeneutic perspective. Initially we will use in research studies through a succession of theoretical frameworks that have contributed to the formation of hermeneutics. Later we will start to a critical analysis of the issues raised, especially by Heidegger and Hans-Georg Gadamer through the existential analytic and philosophical hermeneutics. The problem to be tackled is a question that is approaching the epistemological problem of the human sciences in general: they would understand the result of a methodological framework or an event unveiling the historical content? How is it possible to know historical contents if there is a barrier set by the temporal distance between the author and the interpreter? The Philosophical Hermeneutics has its importance in this work, because it demonstrates an understanding and critical and reflective dialogue with tradition.